Electrode estimation in the acoustic region of the human Cochlea - Polak, Marek; Lorens, Artur; Furmanek, Mariusz; Skarzyński, Henryk (Acta oto-laryngologica, 2020)
Background: In this study, a method to estimate number of electrodes in the acoustic region of Electric Acoustic Stimulation (EAS) subjects was proposed. Aims/Objectives: To develop and validate an anatomy-based method for EAS subjects to estimate the number of electrodes within the acoustic region. Material and methods: The postoperative CTs of adults with various degree of hearing implanted with lateral wall electrodes with mean insertion depth of 23.9 mm (18.0-28.2 mm) and mean insertion angle of 505° (355-695°) were evaluated. Results: The difference between the estimated and measured angle varied between −18 and 25°, with a mean of 0.9°. For the insertion angle of 230° and higher, the maximum difference was 24°. Taking this uncertainty into account, all electrodes in the acoustic region were predicted correctly. Conclusions and significance: The method decides on non-overlapping acoustic and electric stimulation in terms of place in the cochlea. With the accuracy of 0.84 mm for the electrode arrays inserted for more than 230°, the method was sufficient to estimate the exact number of electrodes in the acoustic region of cochlear implantees. The benefit of this method may be in fitting of EAS subjects with some portion of the electrode array in the acoustic region.